2005
DOI: 10.1002/ctpp.200510051
|View full text |Cite
|
Sign up to set email alerts
|

First Principle Thermodynamic and Dynamic Simulations for Dense Quantum Plasmas

Abstract: We present a detailed analysis of temperature-dependent effective quantum pair potentials. These potentials are derived from first-principle path integral Monte Carlo simulations and are accurate even at strong coupling and partial ionization. They can be efficiently used in molecular-dynamics (MD) simulations to obtain accurate thermodynamic and dynamic properties of strongly coupled hydrogen down to the temperatures of about 60 000 K. Furthermore, using spin-dependent pair potentials, dynamic structure facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…We mentioned already the pioneering work of Hansen et al [11]. More recent MD simulations have shown that the use of Kelbg-type effective potentials provides good thermodynamic functions, correlation functions, microfield distributions and, to some extent, also non-equilibrium properties [20][21][22][23][24][25][26].…”
Section: Applications Of Kelbg-type Effective Potentialsmentioning
confidence: 99%
“…We mentioned already the pioneering work of Hansen et al [11]. More recent MD simulations have shown that the use of Kelbg-type effective potentials provides good thermodynamic functions, correlation functions, microfield distributions and, to some extent, also non-equilibrium properties [20][21][22][23][24][25][26].…”
Section: Applications Of Kelbg-type Effective Potentialsmentioning
confidence: 99%
“…It has many properties characteristic of nonlinear waves, especially localized modes and solitons, and beam-driven waves and instabilities. The NLS equation and its variants describe nonlinear physical systems appearing in a wide spectrum of problems in (quantum) plasmas 21 and other fields, for example, in fluids and water waves, ultrafast transmission systems, condensed matter systems, and so on. NLS contains an additional nonlinear term in the Schrödinger equation responsible for the nonlinear effects.…”
Section: Nonlinear Waves In Quantum Plasmasmentioning
confidence: 99%
“…(1.28) also facilitates the verification of numerical solvers and aids in the stability analysis. Discrete nonlinear Schrödinger (DNLS) equations are also important in discrete lattice models in nonlinear optics, 21 always assuming that the applicability conditions of QHD are fulfilled. condensed matter and trapped Bose-Einstein condensates where a numerical evaluation is straightforward using e.g.…”
Section: Nonlinear Waves In Quantum Plasmasmentioning
confidence: 99%
See 2 more Smart Citations